Performance of technology and prospects agribusiness for salacca fruit - Dwi Amiarsi; Edy Mulyono (Buletin Teknologi Pasca Panen, 2013)
The potency of salacca edulis has not been fully utilized yet. Its use is limited as Salacca edulis decoration/parcel, of sweets fruits in syrup (in can or glass bottles). The improvement of fruits quality, the longer shelf life and product diversity can increase the usefulness of the fruits in modern life. Postharvest handling activities generally still has not done well by the farmers and traders. To increase the production of as well as the direction of development of fruits is to implemental quality assurance system that cover post harvest handling is good and right, and distribution. Postharvest handling of fruits through harvesting, collecting, cleaning, sorting and grading, pre-treatment, packaging and storage, transportation, distribution, and display. Technology of processed fruits which is increased the added value, i.e. sweet pickle, chips, fruit in syrup, pickles, edible coating. Abstrak Versi IndonesiaPotensi buah salak belum dimanfaatkan secara maksimal, penggunaannya terbatas sebagai buah meja, parsel, manisan dan buah salak dalam sirup (dikemas kaleng atau botol gelas). Peningkatan mutu buah salak, masa simpan yang lebih lama dan keragaman produk dapat menambah kegunaan buah salak dalam kehidupan modern. Kegiatan penanganan pascapanen umumnya masih belum dilakukan secara baik oleh petani maupun pedagang. Untuk meningkatkan produksi sekaligus sebagai arah pengembangan buah salak adalah dengan menerapkan sistem jaminan mutu yang meliputi cara penanganan pascapanen yang baik dan benar, dan cara distribusi yang baik dan benar. Penanganan pascapanen buah salak melalui kegiatan panen, pengumpulan, pembersihan, sortasi dan grading, perlakuan awal, pengemasan dan penyimpanan, transportasi, distribusi, dan peragaan. Teknologi olahan buah salak untuk peningkatan nilai tambah dapat berupa manisan, keripik, buah dalam sirup, asinan, edible coating.